2015
DOI: 10.1007/s00477-015-1074-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-time correction of water stage forecast using combination of forecasted errors by time series models and Kalman filter method

Abstract: This study modifies a real-time correction method for water stage forecasts (named the RTEC_TS&KF model) using the time series method developed by Wu et al. (Stoch Environ Res Risk Assess 26:519-531, 2012) (named the RTEC_TS model), by incorporating the Kalman filter (KF) model. The RTEC_TS&KF model adjusts the corrected water stage forecasts resulting from the RTEC_TS model by taking into account the uncertainties in the model structure/inputs as well as the measurement bias. In detail, the water stage fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…2, flows at the watershed outlet exhibit significant persistence and time series of streamflows can be represented by an autoregressive model. In addition, a few studies have also demonstrated that, with real-time error correction, AR(1) and AR(2) can significantly enhance the reliability of the forecasted water stages at the 1-, 2-, and 3-h lead time (Wu et al 2012;Shen et al 2015). Thus, we suggest using the AR(2) model as the benchmark series for flood forecasting model performance evaluation.…”
Section: Model Performance Evaluation Using Simulated Seriesmentioning
confidence: 98%
“…2, flows at the watershed outlet exhibit significant persistence and time series of streamflows can be represented by an autoregressive model. In addition, a few studies have also demonstrated that, with real-time error correction, AR(1) and AR(2) can significantly enhance the reliability of the forecasted water stages at the 1-, 2-, and 3-h lead time (Wu et al 2012;Shen et al 2015). Thus, we suggest using the AR(2) model as the benchmark series for flood forecasting model performance evaluation.…”
Section: Model Performance Evaluation Using Simulated Seriesmentioning
confidence: 98%
“…Kalman filtering is a recursive approach involving ideal linear filtering to estimate the state variables of a system. For system modeling, the initial positioning values were used to predict and adjust parameters in each new measurement, obtaining the estimated error in each data update (Shen et al, 2015).…”
Section: Implementation Of the Filtering Algorithmmentioning
confidence: 99%
“…According to the historical data of the research object fitting a curve over time which can analyze the changes more intuitive in the rules, and then extend the curve in the future, which formed a prediction of the future of the data [4]. In recent years, various kinds of time series data prediction method is extracted, according to the different programming models can be divided into: prediction method based on support vector machine, prediction method based on self organizing feature map, prediction method based on extended Calman filter, prediction method based on artificial neural network [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%